In the moment : the art of campaigning in real-time - Himpe, Tom, ....-; Goiris, Pieter, ....- (Leuven : LannooCampus, 2014)
Why should it take 9 months to make an advertisement that only lasts for 30 seconds? The output of the advertising sector is remarkably small. Each year, the average advertising bureau doesn't even produce enough text and photos to fill a single newspaper or TV program. And this in an age when advertising is only as valuable as the public it reaches, the attention it attracts and the connections it creates. #inthemoment introduces you to the secrets of real-time content. Analyzing, planning, creating and spreading content in real-time generates a greater dynamic. You adjust better and you learn as you go.
Keywords: Advertising -- Planning; Advertising; Reclame